OUT OF TIME : LOST ON THE TITANIC - Rinker, Jessica; Stancliffe, Bethany (Kansas City, Missouri : [2020] Andrews McMeel Publishing, 2020)
Allie and Vic Taylor are just regular kids who help out in their parents' antique shop. Until one day, when they find they can travel through time! From Epic! Originals, Out of Time is a middle-grade chapter book series about time-traveling kids who explore important moments in history!
Keywords: children's stories, English; Titanic (Steamship) -- Juvenile fiction; Friendship -- Juvenile fiction